The concepts of Ludwik Fleck and their application to the eukaryotic cell cycle - Stephen Cooper (Studia Historiae Scientiarum, 2017)
The concepts of Ludwik Fleck (1896–1961), a microbiologist, historian, and philosopher of medicine, can be used to analyze the conservative nature of scientific ideas. This is discussed and applied to ideas dominant in the understanding of the eukaryotic cell cycle. These are (a) the G1-phase restriction point as a regulatory element of the mammalian cell cycle, (b) the Rate Change Point proposed to exist in fission yeast, and (c) the proposal that a large number of genes are expressed in a cell-cycle-dependent manner.